2018
DOI: 10.14814/phy2.13881
|View full text |Cite
|
Sign up to set email alerts
|

The impact of exercise training and resveratrol supplementation on gut microbiota composition in high-fat diet fed mice

Abstract: The aim of this study was to examine the effect of exercise training and dietary supplementation of resveratrol on the composition of gut microbiota and to test the hypothesis that exercise training and resveratrol can prevent high‐fat diet (HFD)‐induced changes in the gut microbiota. Mice fed a HFD supplemented with resveratrol (4 g/kg food) were protected against diet‐induced obesity, while exercise trained HFD‐fed animals (running on average 50 km/week) were not. Dietary resveratrol supplementation induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 53 publications
2
29
1
Order By: Relevance
“…Others have also reported that elite athletes have higher alpha diversity than sedentary controls ( 61 ) or that exercise training in mice leads to increased Shannon diversity ( 62 , 63 ). However, in agreement with the current experiment, PA has been shown to have no effect on alpha diversity in mice ( 64 66 ), rats ( 67 ), and humans ( 58 , 68 ). The reasons for these discrepancies are not clear, although multiple factors, such as differences in animal vendors and facilities, DNA extraction methods and sequencing, bioinformatics analysis, and statistical testing methods, are likely involved.…”
Section: Discussionsupporting
confidence: 91%
“…Others have also reported that elite athletes have higher alpha diversity than sedentary controls ( 61 ) or that exercise training in mice leads to increased Shannon diversity ( 62 , 63 ). However, in agreement with the current experiment, PA has been shown to have no effect on alpha diversity in mice ( 64 66 ), rats ( 67 ), and humans ( 58 , 68 ). The reasons for these discrepancies are not clear, although multiple factors, such as differences in animal vendors and facilities, DNA extraction methods and sequencing, bioinformatics analysis, and statistical testing methods, are likely involved.…”
Section: Discussionsupporting
confidence: 91%
“…Others have also reported that elite athletes have higher alpha diversity than sedentary controls (92), or that exercise training in mice leads to increased Shannon diversity (93,94). However, in agreement with the current experiment, PA has been shown to have no effect on alpha diversity in mice (29,95,96), rats (97), and humans (30,98). The reasons for these discrepancies are not clear, though multiple factors such as differences in animal vendors and facilities, DNA extraction methods and sequencing, bioinformatics analysis, and statistical testing methods, are likely involved.…”
Section: Wheel Running Has Limited But Significant Effects On the Intsupporting
confidence: 88%
“…The earliest study found was published in 2008 by Matsumoto et al (57) but was followed by a host of studies aiming to identify the effects of exercise on the gut microbiota (19,. The majority of these studies have investigated the effect of exercise on the gut microbiota in rodents (57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75), though some have studied humans in intervention trials (18,(76)(77)(78)84) and in cross-sectional or observational comparisons of athletes or active individuals and sedentary individuals (19, 79-83, 85, 86).…”
Section: Methodsmentioning
confidence: 99%
“…Although there are similarities in microbial factors shown to be affected by exercise within the literature, directions of the effects are inconsistent, and some studies show contradictory results. For example, while some studies show a reduction in Firmicutes and/or an increase in Bacteroidetes as a result of exercise (58,64,66,70,73,74,81,84), others show the opposite effect (19, 60-62, 68, 71, 81, 86), and others show no effect (69,76,82).…”
Section: The Effect Of Exercise On the Gut Microbiomementioning
confidence: 99%